Online intercultural exchanges through digital storytelling - Sevilla-Pavón, Ana; Nicolaou, Anna (My University, 2017)
This article focuses on the affordances of a digital storytelling project in developing students' language, digital and other skills: learning and innovation, creativity, critical thinking, problem solving, team working, and life and career skills. The project was undertaken by university English for Specific Purposes students and was conducted within an Online Intercultural Exchange between the Cyprus University of Technology and the University of Valencia. Its design was based on a Project-Based Learning (PBL) methodology. It incorporated active learning and multimodal resources and capabilities. The need for transforming language teaching pedagogies was borne in mind, as it is necessary for responding to an era of changes which requires students to be active producers of content, innovative, motivated and engaged in their own learning. The qualitative and quantitative findings were drawn from data gathered by means of an evaluation questionnaire administered to students upon completion of the project.
Keywords: 21st century skills; Affordances; Digital storytelling; Online intercultural exchange; Project-based learning